The relationship between migraine and rosacea: Systematic review and meta-analysis. (June 2018) - Christensen, Casper Emil; Andersen, Frederikke Schelde; Wienholtz, Nita; Egeberg, Alexander; Thyssen, Jacob P; Ashina, Messoud
Objective: To systematically review the association between migraine and rosacea. Background: Migraine is a complex disorder with episodes of headache, nausea, photo- and phonophobia. Rosacea is an inflammatory skin condition with flushing, erythema, telangiectasia, papules, and pustules. Both are chronic disorders with exacerbations of symptoms almost exclusively in areas innervated by the trigeminal nerve. Previous studies found an association between these disorders. We review these findings, provide a meta-analysis, and discuss possible pathophysiological commonalities. Methods: A search through PubMed and EMBASE was undertaken for studies investigating the association between all forms of migraine and rosacea published until November 2016, and meta-analysis of eligible studies. Results: Nine studies on eight populations were identified. Studies differed in methodology and diagnostic process, but all investigated co-occurrence of migraine and rosacea. Four studies were eligible for meta-analysis, resulting in a pooled odds ratio of 1.96 (95% confidence interval 1.41–2.72) for migraine in a rosacea population compared to a non-rosacea population. Conclusion: Our meta-analysis confirmed an association in occurrence of migraine and rosacea. Future studies should specifically investigate possible shared pathophysiological mechanisms between the two disorders.